Kilka uwag o II Zjeździe Niemcoznawców 21–23 listopada 2013 roku - Mackiewicz, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The 2nd German Studies Congress in Wrocław, bringing together historians, Germanists, phi-losophers, sociologists, culture scholars, political scientists, lawyers, experts from other disciplines as well as everybody interested in German studies, was an important event. This scholarly meeting has an open formula, deliberately planned to reach as wide an audience as possible. Doing away with the myth of “serious and elite scholarly congress” in favour of accessibility or even popularity, corresponds, in my opinion, to the main assumption behind the Wrocław meetings, i.e. experience and information sharing as well as integration on the highest level. During the congress the parti-cipants had an opportunity to listen to several dozen papers in more than ten sections divided into thematic panels. In addition to the panel sessions, the participants could take part in a number of associated events — meeting with an author, vernissage or film screenings.
Keywords: Niemcy; Wrocław; kultura; polityka; germanistyka